Internet connectivity disruption in Brazil (Brazil) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Brazil. Data sourced from IODA.
Network Disruption Incident ID: BR-2026-0012. Severity: critical. Confidence: 65%